2022
DOI: 10.1002/cbdv.202200259
|View full text |Cite
|
Sign up to set email alerts
|

Isopentenylated Bibenzyls and Phenolic Compounds from Dendrobium chrysotoxum Lindl

Abstract: Two new isopentenyl bibenzyls, denchrysotonols A and B (1–2), along with 26 known phenolic compounds, were isolated from the stems of cultivated Dendrobium chrysotoxum Lindl. Their chemical structures were clearly elucidated by extensive spectroscopic analysis. Biological evaluation of isolated compounds revealed that phenanthrenes (14, 16–17, 20, and 22) and fluorenone 25 exhibited anti‐inflammatory activities which inhibited nitric oxide (NO) production in LPS‐activated RAW264.7 macrophages with the IC50 val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…Research shows that the levels of compounds from different Dendrobium varied greatly. In D. nobile , the major metabolite types were alkaloids, terpenoids, flavonoids and phenanthrenes, however, in D. chrysotoxum , the largest number of metabolite types belonged to bibenzyls, phenanthrenes and phenolic acids, which was consistent with previous studies [ 55 – 57 ]. Notably, D. nobile stem is abundant and diversified in alkaloids, such as dendrobine, N-isopentenyl-dendrobinium and N-methyldendrobinium, in D. chrysotoxum , bibenzyls and phenanthrenes secondary metabolites were significantly accumulated, such as chrysotobibenzyl, chrysotoxin, moscatilin, and chrysotoxene.…”
Section: Discussionsupporting
confidence: 92%
“…Research shows that the levels of compounds from different Dendrobium varied greatly. In D. nobile , the major metabolite types were alkaloids, terpenoids, flavonoids and phenanthrenes, however, in D. chrysotoxum , the largest number of metabolite types belonged to bibenzyls, phenanthrenes and phenolic acids, which was consistent with previous studies [ 55 – 57 ]. Notably, D. nobile stem is abundant and diversified in alkaloids, such as dendrobine, N-isopentenyl-dendrobinium and N-methyldendrobinium, in D. chrysotoxum , bibenzyls and phenanthrenes secondary metabolites were significantly accumulated, such as chrysotobibenzyl, chrysotoxin, moscatilin, and chrysotoxene.…”
Section: Discussionsupporting
confidence: 92%
“…Research shows that the levels of compounds from different Dendrobium varied greatly. Among them, D. nobile stem is abundant and diversi ed in alkaloids, such as dendrobine, N-isopentenyldendrobinium and N-methyldendrobinium, in D. chrysotoxum, bibenzyls and phenanthrenes secondary metabolites were signi cantly accumulated, such as chrysotobibenzyl, chrysotoxin, moscatilin, and chrysotoxene, which was consistent with previous studies [42][43][44]. In addition, we also found that there was no signi cant difference in the chemical composition of stems and leaves of Dendrobium species, indicating that leaves of Dendrobium species are also essential sources of natural lead compounds [45,46].…”
Section: Quality Oriented Metabolite Ngerprintsupporting
confidence: 91%
“…However, the investigation on secondary metabolisms of planted D. devonianum was limited. Drived by our continuous interests of finding bioactive components from the cultivated Dendrobium species, [7] in this study, we carried out a phytochemical work on D. devonianum collected from greenhouse cultivation base in Mangshi of Yunnan Province. As a result, two new bibenzyl‐phenylpropane hybrids ( Figure 1, 1 – 2 ) and nine known bibenzyls ( 3 – 11 ) were isolated and identified.…”
Section: Introductionmentioning
confidence: 99%